A double‐virally‐inactivated (Intercept–solvent/detergent) human platelet lysate for in vitro expansion of human mesenchymal stromal cells. Issue 6 (25th March 2019) - Barro, Lassina; Su, Yu‐Ting; Nebie, Ouada; Wu, Yu‐Wen; Huang, Yen‐Hua; Koh, Mickey BC; Knutson, Folke; Burnouf, Thierry
Abstract : BACKGROUND: Pooled human platelet lysate (HPL) can replace fetal bovine serum (FBS) as xeno‐free supplement for ex vivo expansion of mesenchymal stromal cells (MSCs). We evaluate here whether a double‐virally‐inactivated HPL (DVI‐HPL) prepared from expired Intercept‐treated platelet concentrates (PCs) and treated by solvent/detergent (S/D) can be used for MSC expansion. STUDY DESIGN AND METHODS: Expired Intercept‐treated PCs in 65% platelet (PLT) additive solution were pooled and subjected to a 1% tri‐ n ‐butyl phosphate/1% Triton X‐45 treatment followed by soybean oil, hydrophobic interaction chromatography purification, and sterile filtration. Bone marrow–derived MSCs (BM‐MSCs) were expanded for four passages in growth medium containing 10% DVI‐HPL, I‐HPL (from Intercept‐PC only), untreated HPL, and FBS. MSC morphology, doubling time, immunophenotype, immunosuppressive activity, and differentiation capacity were compared. RESULTS: Expanded cells had typical spindle morphology and showed higher viability in all HPL conditions than in FBS. The DVI‐HPL and FBS‐expanded cells were morphologically larger than in I‐HPL and HPL supplements. The cumulative population doubling was lower using DVI‐HPL than with HPL and I‐HPL, but significantly higher than using FBS. Immunophenotype was not affected by the supplements used. Immunosuppressive activity was maintained with all supplements. Differentiation capacity into chondrocytes and osteocytes was more effective in DVI‐HPL but less toward adipocytes compared to other supplements. CONCLUSIONS: Human PLT lysate made from Intercept‐PCs subjected to S/D treatment may be an alternative to untreated HPL and to I‐HPL for BM‐MSC expansion. This finding reinforces the potential of HPL as a virally safe alternative to FBS for clinical grade MSC expansion protocols.